Astyanax pirapuan: A new characid species from the upper Rio Paraguay system, Mato Grosso, Central Brazil (Characiformes, Characidae) - Tagliacollo, Victor A. [UNESP]; Britzke, Ricardo [UNESP]; Silva, Gabriel S. C. [UNESP]; Benine, Ricardo C. [UNESP] (Magnolia Press, 2011)
A new characid fish is described herein from tributaries of the Rio Aricá-Mirim, Rio Cuiabá basin, Chapada dos Guimarães, Mato Grosso State, Brazil. Astyanax pirapuan better conforms to the A. scabripinnis species complex and it can be distinguished from other species of this complex by a combination of characters, including 8-9 gill rakers on the upper limb of first branchial arch, 0-1 tooth on the maxillary, 17 to 21 branched anal-fin rays, 35-37 perforated lateral line scales and two humeral spots. Copyright © 2011 · Magnolia Press.
Keywords: Astyanax scabripinnis; Neotropical; taxonomy